An In Vitro Study to Determine the Feasibility of Combining Bone Marrow Concentrate with BST-CarGel as a Treatment for Cartilage Repair. (April 2021) - Snow, Martyn; Williams, Richard; Pagkalos, Joseph; Grover, Liam
Objective: The study aims were to determine whether BST-CarGel, a chitosan scaffold for cartilage repair, can be mixed with bone marrow aspirate concentrate (BMAC) to create a cell seeded implant with comparative properties to standard BST-CarGel mixed with blood. Design: Whole blood and bone marrow were harvested from 12 patients who underwent cartilage repair surgery using BMAC after informed consent. A validated in vitro testing model was used to assess the following 6 conditions: (1) BST-CarGel mixed with whole blood (CG-WB), (2) BST-CarGel mixed with bone marrow (CG-BM), (3) BST-CarGel mixed with bone marrow concentrate (CG-BMAC), (4) whole blood (WB), (5) bone marrow (BM), and (6) bone marrow concentrate and batroxobin (BMAC-BTX). Cell retention and viability within the BST-CarGel/BMAC clots were investigated. Results: In our study, BM and BMAC (processed using the Harvest, SmartPrep2 system and reactivated with batroxibin) when combined with BST-CarGel produced a product that had similar clot contraction, macroscopic properties, and histological appearance to standard BSTCarGel mixed with blood. Mononucleated cells from the BMAC were retained within the scaffold and remained viable until clot dissolution in vitro . Conclusions: By combining BST-CarGel with BMAC in the manner described, bone marrow–derived mononucleated cells can be retained within the chondral defect potentially negating the need for microfracture. Further in vivo work is required to confirm these potential benefits and determine if this combination will result in more durable cartilage repair and improved clinical outcomes.